Mongolia in the world community of civilizations and nations - Popkov, Yuri V.; Tyugashev, Evgenii A. (The New Research of Tuva, 2012)
Basing on the ethnosocial studies of 2009 and 2011 article analyzes the popular and expert opinion’s perception of Mongolian people’s attitude to other nations.
Keywords: Mongolia; civilization; metacivilization; nations; interaction; axiological orientations